Pengaruh Kepemimpinan Transformasional, Komunikasi Antarpribadi dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada Pemerintah Kabupaten Situbondo - Rachman, Alief Rizaldy; Titisari, Purnamie; Paramu, Hadi (Universitas Dr. Soetomo, 2024)
This research aims to determine the effect of transformational leadership, interpersonal communication and organizational commitment on employees performance of Situbondo Regency Government. The approach in this study used a survey method who involves Situbondo Regency Government employees, specifically in office unit as DBHCHT recipient. The purposive sampling method was used to determine the research sample and obtained 104 respondents who suitable with the criteria. The variable measurement scale in this research questionnaire uses a semantic scale and is analyzed using multiple linear regression analysis and hypothesis testing methods. The benefit of this research is to get to know about specific impact of three variables that affect work performance so it will help leaders of the government to maximalize employee work performance. The research results show that respondents responded positively to each statement item to measure the variable. Based on further analysis of primary data using the SPSS Software, it can be concluded that transformational leadership, interpersonal communication, and organizational commitment have a significant positive influence on employee performance. Leaders who have been able to implement a transformative attitude, warm and professional employee communication, and high commitment to the organization produce employee performance that can be said to be good.